Advertising Affects Public Perception of Brands The Ads Affect the Public's Perception of Brands - Adillah Siti Sayyidah; Galuh Alif Rachman (Trigin Publisher, 2020)
This study aims to find out how advertising can affect people's perceptions of brands. The research method used is quantitative research with descriptive analysis based on questionnaires. The subjects studied were 10 respondents from people around the researcher who filled out the questionnaire data link via the Google form that had been distributed by us as researchers. Analysis of the research data resulted in the development of the theory of Hypodermic Needle Theory or Hypodermic Needle Theory where advertisements can influence the audience by continuously sending messages so that the messages conveyed enter the audience's unconscious. A total of 10 respondents expressed their opinion, from where they often see advertisements on social media to how advertisements can affect their perception of a brand. In the end, this study proves that advertising can influence people's perceptions of brands.